Implementation Of Writing Skills Based On The Independent Curriculum In The seventh Grade Of MTsN 1 Kediri City - Naimah, Ilfa; Sholihuddin, Ahmad; Faiqoh, Putri Kholida (Universitas Islam Tribakti Lirboyo, Kediri, 2024)
Learning writing skill in the seventh grade of MTsN 1 Kediri City is one of the language skills where students are expected to be able to develop Arabic writing skills well and master the basics of Arabic writing correctly. The research aims to find out the implementation of kitabah learning based on the independent curriculum and to find out the obstacles experienced by students during kitabah learning in the seventh grade of MTsN 1 Kediri City. The method used in this study is a qualitative research method that is descriptive. The research data was collected from primary data and secondary data sources with collection techniques using observation, interviews and documentation. The data analysis techniques used include data reduction, data presentation and conclusion drawing. The results of this research show that: (1) In the implementation of writing learning based on the independent curriculum, teachers have implemented differentiated learning by forming working groups with different student abilities. (2) Obstacles to the Implementation of Kitabah Learning, namely linguistic problems and nonlinguistic problems. As for the obstacles to the implementation of the independent curriculum, namely the lack of package books available in the library. So that not all students have books.